Constraining Resolved Extragalactic R21 Variation with Well-calibrated ALMA Observations - Jakob den Brok; Elias K. Oakes; Adam K. Leroy; Eric W. Koch; Antonio Usero; Erik W. Rosolowsky; Frank Bigiel; Jiayi Sun; Hao He; Ashley T. Barnes; Yixian Cao; Fu-Heng Liang; et al. (The Astrophysical Journal, 2025)
CO(1–0) and CO(2–1) are commonly used as bulk molecular gas tracers. The CO line ratios (especially CO(2–1)/CO(1–0)– R _21 ) vary within and among galaxies, yet previous studies on R _21 and alike often rely on measurements constructed by combining data from facilities with substantial relative calibration uncertainties that have the same order as physical line ratio variations. Hence, robustly determining systematic R _21 variations is challenging. Here, we compare CO(1–0) and CO(2–1) mapping data from ALMA for 14 nearby galaxies, at a common physical resolution of 1.7 kpc. Our data set includes new ALMA (7 m+TP) CO(1–0) maps of 12 galaxies. We investigate R _21 variation to understand its dependence on global galaxy properties, kiloparsec-scale environmental factors, and its correlation with star formation rate (SFR) surface density and metallicity. We find that the galaxy-to-galaxy scatter is 0.05 dex. This is lower than previous studies, which reported over 0.1 dex variation, likely reflecting significant flux calibration uncertainties in single-dish surveys. Within individual galaxies, R _21 has a typical mean value of ∼0.64 and 0.1 dex variation, with an increase to ∼0.75 toward galactic centers. We find strong correlations between R _21 and various galactic parameters, particularly SFR surface density, which shows a power-law slope of 0.10–0.11 depending on the adopted binning/fitting methods. Our findings suggest that, for studies covering main-sequence galaxy samples, assuming a fixed R _21 = 0.64 does not significantly bias kiloparsec-scale molecular gas mass estimates from CO(2–1). Instead, systematic uncertainties from flux calibration and the CO-to-H _2 conversion factor account for more systematic scatter of CO-derived molecular gas properties.